Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Apologie für das Nebensächliche. Prinzipien einer intersektional orientierten Unterrichtsmodel-lierung am Beispiel von Aneignungsperspektiven zu einer jugendpopulären Fernsehserie - Kißling, Magdalena (Rassismussensibler Literaturunterricht – Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten)

Differenzkonstruktionen in Explikation und Beiläufigkeit. Vergleichende Betrachtungen zur Wirkungsästhetik bei Fünftklässler:innen hinsichtlich unterschiedlichen kinderliterarischen Erzählens von Diversität - Kißling, Magdalena ("So viel Größenwahn muss sein!" Kinderliteratur - Schule - Gesellschaft)

Diskriminierungssensible Methoden. Neue Lernwege im kulturwissenschaftlich ausgerichteten Literaturunterricht - Kißling, Magdalena (Neue Perspektiven einer kulturwissenschaftlich orientierten Literaturdidaktik)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batterieghäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Experimentelle Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

Effizientes Lösen von Klebverbindungen in der Fahrzeuginstandsetzung - Chudalla, Nick; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

Zum Verständnis von Innovation und Transfer in einer vernetzten Berufsbildungspraxis. Ergebnisse einer übergreifenden Interviewstudie - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Optimizing the Streaming of Sensor Data with Approximate Communication - Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Asian Test Symposium (ATS'23), October 2023)

„Go with the flow?!“ Einblicke in Forschungsansatz und erste Ergebnisse des Begleitforschungsprojekts ITiB - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Packings and Steiner systems in polar spaces - Schmidt, Kai-Uwe; Weiß, Charlene (Combinatorial Theory)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-Steiner system in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $n$-spaces such that each totally isotropic $t$-space is contained in exactly one member of $Y$. Nontrivial examples are known only for $t=1$ and $t=n-1$. We give an almost complete classification of such $t$-Steiner systems, showing that such objects can only exist in some corner cases. This classification result arises from a more general result on packings in polar spaces.

Existence of small ordered orthogonal arrays - Schmidt, Kai‐Uwe; Weiß, Charlene (Journal of Combinatorial Designs)
We show that there exist ordered orthogonal arrays, whose sizes deviate from the Rao bound by a factor that is polynomial in the parameters of the ordered orthogonal array. The proof is nonconstructive and based on a probabilistic method due to Kuperberg, Lovett and Peled.

Linear programming bounds in classical association schemes - Weiß, Charlene
Digital communications relies heavily on the usage of different types of codes. Prominent codes nowadays are rank-metric codes and subspace codes - the q-analogs of binary codes and binary codes with constant weight. All these codes can be viewed as subsets of classical association schemes. A central coding-theoretic problem is to derive upper bounds for the size of codes. This thesis investigates Delsartes powerful linear program whose optimum is precisely such a bound for codes in association schemes. The linear programs for binary codes and binary constant-weight codes have been extensively studied since the 1970s, but their optimum is still unknown. We determine in a unified way the optimum of the linear program in several ordinary q-analogs as well as in their affine counterparts. In particular, bounds and constructions for codes in polar spaces are established, where the bounds are sharp up to a constant factor in many cases. Moreover, based on these results, an almost complete classification of Steiner systems in polar spaces is provided by showing that they could only exist in some corner cases.

Nontrivial $t$-designs in polar spaces exist for all $t$ - Weiß, Charlene (arXiv:2311.08288)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space over $\mathbb{F}_p$ equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-$(n,k,λ)$ design in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $k$-spaces such that each totally isotropic $t$-space is contained in exactly $λ$ members of $Y$. Nontrivial examples are currently only known for $t≤ 2$. We show that $t$-$(n,k,λ)$ designs in polar spaces exist for all $t$ and $p$ provided that $k>\frac{21}{2}t$ and $n$ is sufficiently large enough. The proof is based on a probabilistic method by Kuperberg, Lovett, and Peled, and it is thus nonconstructive.

"Fotonotizen". documenta fifteen - Autsch, Sabiene (Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022))

"More human than human.“ – Biopolitik und Geschlecht in Alex Garlands Ex Machina - Puscher, Sahra (Biopolitik(en) in Literatur, Film und Serie. Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute)

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

SEMOK-1-2: Selbstwahrnehmung motorischer Basiskompetenzen in der ersten und zweiten Primarschulklasse. Manual - Bretz, Kathrin; Strotmeyer, Anne; Herrmann, Christian
Um die Selbstwahrnehmung motorischer Basiskompetenzen bei Kindern der 1. und 2. Klasse zu erfassen, wurde ein illustriertes Instrument entwickelt. Das Instrument orientiert sich am MOBAK-1-2 Instrument, mit welchem die motorischen Basiskompetenzen von Kindern getestet werden. Das Manual enthält die Instruktionen sowie die illustrieren Antwortoptionen und Testaufgaben.

Designbasierte Forschung in der beruflichen Bildung:Perspektiven aus Wissenschaft, Praxis und Politik. - Ertl, Hubert; Kremer, H.-Hugo; Kundisch, Heike; Sloane, Peter F. E. (Wissenschaft trifft Praxis - Designbasierte Forschung in der beruflichen Bildung.)
Designbasierte Forschung umfasst verschiedene Ausprägungsformen von Forschungsprozessen, die auf die Entwicklung und Implementation von Innovationen abzielen. Mit der Anwendung von designbasierten Ansätzen haben Forscherinnen und Forscher den Anspruch, sich an der Lösung praktischer Problemlagen zu beteiligen; dies ist ein wichtiger Ausgangspunkt für die Anlage von Forschungsprozessen und -programmen. Häufig geht es um bisher wenig strukturierte, aktuelle Probleme in der Berufsbildungspraxis, was wiederum bedeutsam für das Aufeinandertreffen und die Zusammenarbeit von Wissenschaft und Praxis ist. Der vorliegende Band nimmt die Vielfalt designbasierter Forschung auf und dokumentiert, ergänzt durch Visualisierungen, die Beiträge des AG BFN Forums „Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung“, welches in einem digitalen Format an der Universität Paderborn stattfand.

Recalibration of limits to growth: An update of the World3 model - Nebel, Arjuna; Kling, Alexander; Willamowski, Ruben; Schell, Tim (Journal of Industrial Ecology)
Abstract After 50 years, there is still an ongoing debate about the Limits to Growth (LtG) study. This paper recalibrates the 2005 World3‐03 model. The input parameters are changed to better match empirical data on world development. An iterative method is used to compute and optimize different parameter sets. This improved parameter set results in a World3 simulation that shows the same overshoot and collapse mode in the coming decade as the original business as usual scenario of the LtG standard run. The main effect of the recalibration update is to raise the peaks of most variables and move them a few years into the future. The parameters with the largest relative changes are those related to industrial capital lifetime, pollution transmission delay, and urban‐industrial land development time.
Keywords: General Social Sciences; General Environmental Science

Wie wir die mittlere Führungsebene als Transformationsbegleiter:innen an Schulen stärken können - Kundisch, Heike (Magazin des Forum Bildung Digitalisierung)

KI in der Schule und Bildungsgerechtigkeit. Blog-Beitrag im fiete.ai-Blog. - Eickelmann, Birgit

Hall mobilities and sheet carrier densities in a single LiNbO3 conductive ferroelectric domain wall - Beccard, Henrik; Beyreuther, Elke; Kirbus, Benjamin; Seddon, Samuel D.; Rüsing, Michael; Eng, Lukas M. (Physical Review Applied)
In the last decade, conductive domain walls (CDWs) in single crystals of the uniaxial model ferroelectric lithium niobate (LiNbO3; LNO) have been shown to reach resistances more than 10 orders of magnitude lower than the resistance of the surrounding bulk, with charge carriers being firmly confined to sheets with a width of a few nanometers. LNO is thus currently witnessing increased attention because of its potential in the design of room-temperature nanoelectronic circuits and devices based on such CDWs. In this context, the reliable determination of the fundamental transport parameters of LNO CDWs, in particular the 2D charge carrier density n2D and the Hall mobility μH of the majority carriers, is of great interest. In this contribution, we present and apply a robust and easy-to-prepare Hall-effect measurement setup by adapting the standard four-probe van der Pauw method to contact a single, hexagonally shaped domain wall that fully penetrates the 200-μm-thick LNO bulk single crystal. We then determine n2D and μH for a set of external magnetic fields B and prove the expected cosinelike angular dependence of the Hall voltage. Lastly, we present photoinduced-Hall-effect measurements of one and the same DW, by determining the impact of super-band-gap illumination on n2D.
Keywords: General Physics and Astronomy

Rezension zu Dagmar Abfalter und Rosa Reitsamer (Hg.) (2022) »Music as Labour – Inequalities and Activism in the Past and Present.« - Troike, Manuel (SAMPLES)

Do People Recover from Algorithm Aversion? An Experimental Study of Algorithm Aversion over Time - Leffrang, Dirk; Bösch, Kevin; Müller, Oliver (Hawaii International Conference on System Sciences)
Optimal decision making requires appropriate evaluation of advice. Recent literature reports that algorithm aversion reduces the effectiveness of predictive algorithms. However, it remains unclear how people recover from bad advice given by an otherwise good advisor. Previous work has focused on algorithm aversion at a single time point. We extend this work by examining successive decisions in a time series forecasting task using an online between-subjects experiment (N = 87). Our empirical results do not confirm algorithm aversion immediately after bad advice. The estimated effect suggests an increasing algorithm appreciation over time. Our work extends the current knowledge on algorithm aversion with insights into how weight on advice is adjusted over consecutive tasks. Since most forecasting tasks are not one-off decisions, this also has implications for practitioners.
Keywords: Algorithm aversion; Time series; Decision making; Advice taking; Forecasting

AI Washing: The Framing Effect of Labels on Algorithmic Advice Utilization - Leffrang, Dirk (International Conference on Information Systems)
Many researchers and practitioners see artificial intelligence as a game changer compared to classical statistical models. However, some software providers engage in “AI washing”, relabeling solutions that use simple statistical models as AI systems. By contrast, research on algorithm aversion unsystematically varied the labels for advisors and treated labels such as "artificial intelligence" and "statistical model" synonymously. This study investigates the effect of individual labels on users' actual advice utilization behavior. Through two incentivized online within-subjects experiments on regression tasks, we find that labeling human advisors with labels that suggest higher expertise leads to an increase in advice-taking, even though the content of the advice remains the same. In contrast, our results do not suggest such an expert effect for advice-taking from algorithms, despite differences in self-reported perception. These findings challenge the effectiveness of framing intelligent systems as AI-based systems and have important implications for both research and practice.
Keywords: Artificial Intelligence; Algorithm Appreciation; Framing; Advice-taking; Expertise

The Broken Leg of Algorithm Appreciation: An Experimental Study on the Effect of Unobserved Variables on Advice Utilization - Leffrang, Dirk (Wirtschaftsinformatik Conference)
Despite the widespread use of machine learning algorithms, their effectiveness is limited by a phenomenon known as algorithm aversion. Recent research concluded that unobserved variables can cause algorithm aversion. However, the impact of an unobserved variable on algorithm aversion remains unclear. Previous studies focused on situations where humans had more variables available than algorithms. We extend this research by conducting an online experiment with 94 participants, systematically varying the number of observable variables to the advisor and the advisor type. Surprisingly, our results did not confirm that an unobserved variable had a negative effect on advice-taking. Instead, we found a positive impact in an algorithm appreciation scenario. This study provides new insights into the paradoxical behavior in which people weigh advice more despite having fewer variables, as they correct for the advisor's errors. Practitioners should consider this behavior when designing algorithms and account for user correction behavior.
Keywords: Algorithm aversion; Data; Decision-making; Advice-taking; Human-Computer Interaction

Diagnostische Potentiale von Lernaufgaben im Sachunterricht fach- und entwicklungsbezogen analysieren und nutzbar machen - Schroeder, René; Franzen, Katja; Reh, Anne (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Quellen der Selbstwirksamkeitsüberzeugungen von Lehramtsstudierenden im Zusammenhang mit der Gestaltung von inklusivem Unterricht - Görel, Gamze; Franzen, Katja; Hellmich, Frank

Primary school teachers' perspectives on the quality of inclusive education - Görel, Gamze; Franzen, Katja; Hellmich, Frank (Teachers and Teaching)

Event Recommendations through the Lens of Vision and Language Foundation Models - Halimeh, Haya; Freese, Florian; Müller, Oliver (Workshop on Recommenders in Tourism, co-located with the 17th ACM Conference on Recommender Systems)
Recommender systems now span the entire customer journey. Amid the multitude of diversified experi- ences, immersing in cultural events has become a key aspect of tourism. Cultural events, however, suffer from fleeting lifecycles, evade exact replication, and invariably lie in the future. In addition, their low standardization makes harnessing historical data regarding event content or past patron evaluations intricate. The distinctive traits of events thereby compound the challenge of the cold-start dilemma in event recommenders. Content-based recommendations stand as a viable avenue to alleviate this issue, functioning even in scenarios where item-user information is scarce. Still, the effectiveness of content- based recommendations often hinges on the quality of the data representation they build upon. In this study, we explore an array of cutting-edge uni- and multimodal vision and language foundation models (VL-FMs) for this purpose. Next, we derive content-based recommendations through a straightforward clustering approach that groups akin events together, and evaluate the efficacy of the models through a series of online user experiments across three dimensions: similarity-based evaluation, comparison-based evaluation, and clustering assignment evaluation. Our experiments generated four major findings. First, we found that all VL-FMs consistently outperformed a naive baseline of recommending randomly drawn events. Second, unimodal text-based embeddings were surprisingly on par or in some cases even superior to multimodal embeddings. Third, multimodal embeddings yielded arguably more fine-grained and diverse clusters in comparison to their unimodal counterparts. Finally, we could confirm that cross event interest is indeed reliant on the perceived similarity of events, resonating with the notion of similarity in content-based recommendations. All in all, we believe that leveraging the potential of contemporary FMs for content-based event recommendations would help address the cold-start problem and propel this field of research forward in new and exciting ways.

Early Depression Detection with Transformer Models: Analyzing the Relationship between Linguistic and Psychology-Based Features - Halimeh, Haya; Caron, Matthew; Müller, Oliver (Hawaii International Conference on System Sciences)
Clinical depression is a serious mental disorder that poses challenges for both personal and public health. Millions of people struggle with depression each year, but for many, the disorder goes undiagnosed or untreated. Over the last decade, early depression detection on social media emerged as an interdisciplinary research field. However, there is still a gap in detecting hesitant, depression-susceptible individuals with minimal direct depressive signals at an early stage. We, therefore, take up this open point and leverage posts from Reddit to fill the addressed gap. Our results demonstrate the potential of contemporary Transformer architectures in yielding promising predictive capabilities for mental health research. Furthermore, we investigate the model’s interpretability using a surrogate and a topic modeling approach. Based on our findings, we consider this work as a further step towards developing a better understanding of mental eHealth and hope that our results can support the development of future technologies.
Keywords: Social Media and Healthcare Technology; early depression detection; liwc; mental health; transfer learning; transformer architectures

Analyzing the Needs of Ukrainian Refugees on Telegram in Real-Time: A Machine Learning Approach - Reimann, Raphael; Caron, Matthew (Wirtschaftsinformatik)
The humanitarian crisis resulting from the Russian invasion of Ukraine has led to millions of displaced individuals across Europe. Addressing the evolving needs of these refugees is crucial for hosting countries and humanitarian organizations. This study leverages social media analytics to supplement traditional surveys, providing real-time insights into refugee needs by analyzing over two million messages from Telegram, a vital platform for Ukrainian refugees in Germany. We employ Natural Language Processing techniques, including language identification, sentiment analysis, and topic modeling, to identify well-defined topic clusters such as housing, financial and legal assistance, language courses, job market access, and medical needs. Our findings also reveal changes in topic occurrence and nature over time. To support practitioners, we introduce an interactive web-based dashboard for continuous analysis of refugee needs.

Verfahrensentwicklung zur einstufigen Herstellung von biegebelastbaren Hybridstrukturen im Fließpressprozess - Stallmeister, Tim
Hybridstrukturen bieten bei Anwendungen mit Biegebeanspruchung ein großes Leichtbaupotenzial, erfordern jedoch komplexe und zum Teil mehrschrittige Fertigungsverfahren. In dieser Arbeit wird ein Verfahren entwickelt, das auf Basis des Fließpressprozesses biegebelastbare Hybridbalken in einem Schritt herstellt. Dazu wird ein Versuchsträger entwickelt, der die Komplexität von Realbauteilen abbildet und für zerstörende sowie zerstörungsfreie Charakterisierungsmethoden geeignet ist. Der Versuchsträger besteht aus einer funktionalisierten Kernstruktur aus Glasfasermattenverstärktem Polypropylen und äußeren Metallgurten aus Stahl- und Aluminiumlegierungen, die mit einem Haftvermittlerfilm versehen sind. Anhand des Versuchsträgers wird ein Fließpresswerkzeug und eine instrumentierte Fertigungsanlage entwickelt, mit der die Hybridstrukturen prototypisch hergestellt werden. Zur Prozessoptimierung wird die Verbindung mechanisch und optisch auf Probenebene analysiert. Weiterhin erfolgen Bauteiluntersuchungen anhand von Dreipunktbiegetests, mit denen das strukturelle Verhalten der Hybridbalken charakterisiert wird. Es wird festgestellt, dass sich mit dem einstufigen Fließpressverfahren sehr gute Verbundfestigkeiten erzielen lassen. Die Temperatur- und Druckführung weisen dabei einen großen Einfluss auf das Ergebnis auf. Anhand der Bauteiluntersuchungen wird bestätigt, dass mit dem entwickelten Verfahren Hybridbalken in nur einem Schritt gefertigt werden können, die vergleichbare mechanische Eigenschaften zu Hybridstrukturkonzepten aus mehrschrittigen Fertigungsverfahren aufweisen.

Regenerative Energien für einen effizienten Betrieb von Presshärtelinien - Knorr, Lukas; Jungeilges, André; Pfeifer, Florian; Burmeister, Sascha Christian; Meschede, Henning

Possibilities of Sustainable Heating Methods for Press Hardening Processes - Jungeilges, André

Untersuchung energieeffizienter und serientauglicher Erwärmungsstrategien mittels resistiver Erwärmung für den Presshärteprozess - Kaiser, Maximilian Alexander; Reitz, Alexander; Konrad, Stefan; Meyer, Thomas; Marten, Thorsten; Tröster, Thomas (Workshop Warmblechumformung)
Bei der Herstellung materialeffizienter Bauteile aus presshärtbaren Stählen für den Leichtbau sind nachhaltige und energieschonende Produktionsverfahren ein wichtiger Bestandteil der industriellen Prozesskette. Mittels direkter resistiver Erwärmung basierend auf dem Jouleschen Gesetz können Platinen energieeffizient, flexibel, bedarfsgerecht und „On Demand“ erwärmt werden. Restriktionen des Verfahrens ergaben sich bisher aus den realisierbaren Platinengeometrien. Ferner fehlten serientaugliche Konzepte zur automatisierten Fertigung resistiv erwärmter Bauteile. Durch ein neuentwickeltes Verfahren wird die resistive Schnellerwärmung von komplexen, umformtechnisch optimierten Bauteilen ermöglicht, wodurch eine vielfältige industrielle Nutzung realisiert werden kann. Aus diesem Grund wurde das neue Verfahren zur energieeffizienten Erwärmung anhand des Presshärteprozesses untersucht. Dazu wurde das Verfahren zunächst auf Probenebene verifiziert und innovative Erwärmungsstrategien durch die Modifizierung des Stromflusses untersucht. Weiterhin wurden prozessnahe Umformversuche durchgeführt und analysiert. Der Fokus der Untersuchungen lag auf der Prozesstechnik insbesondere der Homogenität der Temperaturverteilung sowie den erzeugten mechanischen Eigenschaften der Bauteile.
Keywords: Presshärten; resistive Schnellerwärmung; Energieeffizienz

More Isn’t Always Better – Measuring Customers’ Preferences for Digital Process Transparency - Brennig, Katharina; Müller, Oliver (Hawaii International Conference on System Sciences)
Digital technologies have made the line of visibility more transparent, enabling customers to get deeper insights into an organization’s core operations than ever before. This creates new challenges for organizations trying to consistently deliver high-quality customer experiences. In this paper we conduct an empirical analysis of customers’ preferences and their willingness-to-pay for different degrees of process transparency, using the example of digitally-enabled business-to-customer delivery services. Applying conjoint analysis, we quantify customers’ preferences and willingness-to-pay for different service attributes and levels. Our contributions are two-fold: For research, we provide empirical measurements of customers’ preferences and their willingness-to-pay for process transparency, suggesting that more is not always better. Additionally, we provide a blueprint of how conjoint analysis can be applied to study design decisions regarding changing an organization’s digital line of visibility. For practice, our findings enable service managers to make decisions about process transparency and establishing different levels of service quality.
Keywords: Digital Services; Line of Visibility; Process Transparency; Customer Preferences; Conjoint Analysis

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Algorithmica)
Abstract Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the server cloud scheduling problem, in which the jobs have to be processed either on a single local machine or on one of infinitely many cloud machines. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server and the other in the cloud. The server processes jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS for the makespan objective for graphs with a constant source and sink dividing cut and strong hardness for the case with unit processing times and delays.
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

A Process Mining Maturity Model: Enabling Organizations to Assess and Improve their Process Mining Activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (European Conference on Information Systems)
Organizations employ process mining to discover, check, or enhance process models based on data from information systems to improve business processes. Even though process mining is increasingly relevant in academia and organizations, achieving process mining excellence and generating business value through its application is elusive. Maturity models can help to manage interdisciplinary teams in their efforts to plan, implement, and manage process mining in organizations. However, while numerous maturity models on business process management (BPM) are available, recent calls for process mining maturity models indicate a gap in the current knowledge base. We systematically design and develop a comprehensive process mining maturity model that consists of five factors comprising 23 elements, which organizations need to develop to apply process mining sustainably and successfully. We contribute to the knowledge base by the exaptation of existing BPM maturity models, and validate our model through its application to a real-world scenario.

Scheduling with Many Shared Resources - Deppert, Max A.; Jansen, Klaus; Maack, Marten; Pukrop, Simon; Rau, Malin (2023 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

Text-Aware Predictive Process Monitoring of Knowledge-Intensive Processes: Does Control Flow Matter? - Brennig, Katharina; Benkert, Kay; Löhr, Bernd; Müller, Oliver (Business Process Management Workshops)

„FInDig“: Fach – Inklusion – Digitalisierung vernetzen. Ein Planungs- und Reflexionsmodell für die Lehrkräftebildung - Häsel-Weide, Uta; Schmidt, R.; Büker, Petra (Zeitschrift für Schul- Und Professionsentwicklung. (PFLB))

The Equivocal Image of Young Social Enterprises - How Self- vs. Other-Oriented Values Influence External Perceptions - Yahyaoui, Y.; Jakob, E.A.; Steinmetz, Holger; Wehner, M.C.; Isidor, R.; Kabst, Rüdiger (Nonprofit Management & Leadership)

Flexible Automation through Robot-Assisted Mechanical Joining in Small Batches - Neumann, Stefan; Wippermann, Jan; Meschut, Gerson; Stepputat, Marten; Beuss, Florian; Flügge, Wilko

Life, Theory, and Group Identity in Hannah Arendt's Thought - Robaszkiewicz, Maria Anna (Arendt Studies)
Keywords: Energy Engineering and Power Technology; Fuel Technology

Reclaiming the Public Space: Critical Phenomenology of Women’s Revolutions in Dark Times - Robaszkiewicz, Maria Anna (Journal of the British Society for Phenomenology)
Keywords: Philosophy

TemporalFC: A Temporal Fact Checking Approach over Knowledge Graphs - Qudus, Umair; Röder, Michael; Kirrane, Sabrina; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2023)
Verifying assertions is an essential part of creating and maintaining knowledge graphs. Most often, this task cannot be carried out manually due to the sheer size of modern knowledge graphs. Hence, automatic fact-checking approaches have been proposed over the last decade. These approaches aim to compute automatically whether a given assertion is correct or incorrect. However, most fact-checking approaches are binary classifiers that fail to consider the volatility of some assertions, i.e., the fact that such assertions are only valid at certain times or for specific time intervals. Moreover, the few approaches able to predict when an assertion was valid (i.e., time-point prediction approaches) rely on manual feature engineering. This paper presents TEMPORALFC, a temporal fact-checking approach that uses multiple sources of background knowledge to assess the veracity and temporal validity of a given assertion. We evaluate TEMPORALFC on two datasets and compare it to the state of the art in fact-checking and time-point prediction. Our results suggest that TEMPORALFC outperforms the state of the art on the fact-checking task by 0.13 to 0.15 in terms of Area Under the Receiver Operating Characteristic curve and on the time-point prediction task by 0.25 to 0.27 in terms of Mean Reciprocal Rank. Our code is open-source and can be found at https://github.com/dice-group/TemporalFC.
Keywords: temporal fact checking · ensemble learning · transfer learning · time-point prediction · temporal knowledge graphs

Impact of the Reformation on Protestant–Jewish dialogue in Germany - Pinsch, Jan Christian (1523. The first martyrs of the Reformation)

Wird es die richtige Schule für mein Kind sein? - Herding, Jana (Die Grundschulzeitschrift)

'He'd seen it in the words of Owen and Brooke': The Influence of Great War Poetry on Post-Millennium Soldier Poetry - Behler, Felix (Anglica: An International Journal of English Studies)

Politisch-humanistische Positionen in Reisenarrativen über Frankreich der 1920er und 1930er Jahre. "La lumière" - Joseph Roths poetischer und medienreflexiver Humanismus - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa)

Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa. Eine Einleitung - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa)

Déjà vu. Sebald wiederlesen - Öhlschläger, Claudia (Nebelflecken und das Unbeobachtete. Neue Forschungsansätze zum Werk W.G. Sebalds im 20. Todesjahr.)

Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa

Rezension: Evelyn Dueck und Sandro Zanetti (Hg.): Mitdenken. Paul Celans Theorie der Dichtung heute, Heidelberg: Winter 2022 - Spener, Anna Maria (Celan-Perspektiven 2022)

Teachers‘ collective efficacy with regard to inclusive practices – Characterising a new scale and international results from Canada, Germany, & Switzerland - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline; Loreman, Tim; Sharma, Umesh

Emotional-motivationales Erleben im Zusammenhang mit selbstbestimmtem Lernen im inklusiven naturwissenschaftlichen Grundschulunterricht - Knickenberg, Margarita

How do attitudes and self-efficacy predict teachers‘ intentions to teach in inclusive classrooms? A cross-national comparison across five countries - Sahli Lozano, Caroline; Wüthrich, Sergej; Kullmann, Harry; Knickenberg, Margarita

Kulturerbe – global – regional – lokal. Wechselwirkungen und Zuschreibungen - Seng, Eva- Maria (Welt – Stadt – Land – Erbe. Denkmalpflege zwischen höchsten Ansprüchen und Pragmatismus. Digitale Jahrestagung der Vereinigung der Denkmalfachämter in den Ländern)

Grischa Vercamer Hochmittelalterliche Herrschaftspraxis im Spiegel der Geschichtsschreibung. Vorstellungen von „guter“ und „schlechter“ Herrschaft in England, Polen und dem Reich im 12./13. Jahrhundert - Bröker, Christina (Jahrbuch für Regionalgeschichte)

Zornige Schwüre und maßlose Freude - London als emotionaler Trigger für den englischen Herrscher Heinrich III. (1216-1272)? - Bröker, Christina (Herrscher in der Metropole. Spannungsfelder zwischen politischer Zentralität und urbaner Diversität in Antike und Mittelalter)

Was sind Rahm(ung)en? - Hoyer, Isabelle; Reis, Oliver; Roose, Hanna (Religionsunterricht und seine Rahmungen)

Der Lehrkörper der Lehrkraft - Hoyer, Isabelle (Religionsunterricht und seine Rahmungen)

Fallarbeit im OER-Format: Die Lehr-/ Lernumgebung inklud.nrw zur Entwicklung inklusions- und digitalisierungsbezogener Kompetenzen in der Grundschullehrkräftebildung - Büker, Petra; Kamin, Anna-Maria; Becker, Veronika; Glawe, Katrin; Herding, Jana; Schaper, Franziska; Stets, Mona (Nachhaltige Bildung in der Grundschule)

Inklusions- und digitalisierungsbezogene Kompetenzen im Lehramtsstudium erwerben – Konzeption, Erprobung und Evaluation der Lehr-/Lernumgebung inklud.nrw - Kamin, Anna-Maria; Büker, Petra; Glawe, Katrin; Herding, Jana; Menke, Insa; Schaper, Franziska (Inklusion digital! Chancen und Herausforderungen inklusiver Bildung im Kontext von Digitalisierung)

Grundschullehramt zwischen Professionalität und De-Professionalisierung. Herausforderungen der Lehrkräftequalifizierung für eine hochwertige grundlegende Bildung in der Grundschule - Rank, Astrid; Büker, Petra; Miller, Susanne; Martschinke, Sabine (Erziehungswissenschaft)
Keywords: General Medicine

Diagnostische Fallarbeit anhand des Vielfaltstableaus. Vermittlung eines zeitgemäßen Umgangs mit Heterogenität durch synergetische Verknüpfung der Querschnittsaufgaben Inklusion und Digitalisierung. Impulsbeitrag an der Tagung: Kinder und Jugendliche in ihrer Vielfalt fördern der Qualitäts- und UnterstützungsAgentur – Landesinstitut für Schule (QUA-LiS NRW) in Dortmund. - Büker, Petra; Herding, Jana
Dezember 2023

Hochschullernwerkstätten als Möglichkeitsräume für forschendes Lernen – Gemeinsame Reflexion von aktuellen Erfahrungen und Befunden aus drei Lernwerkstätten in Paderborn. Symposium auf der Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Siegen - Büker, Petra; Höke, Julia; Isele, Patrick; Kottmann, Brigitte; Ellersiek, Annchristin; Glawe, Katrin
September 2023

Grundschullehramt zwischen Professionalität und drohender De-Professionalisierung: Aktuelle Herausforderungen der Lehrkräftequalifizierung für eine hochwertige grundlegende Bildung in der Grundschule. Special Interest Group auf der Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Siegen - Büker, Petra; Rank, Astrid; Miller, Susanne; Martschinke, Sabine
September 2023

Neue Wege in der Lehrer:innenbildung: Inklusion und Digitalisierung im OER-Format lernen, weiterentwickeln und verbreiten (InDigO). Konferenztrack auf der TURN Conference „Prototyp Zukunft – Lösungen für transformative Lehre teilen“ an der TH Köln - Büker, Petra; Gantenbrink, Sina; Tibbe, Tim; Herding, Jana; Kamin, Anna-Maria; Deimann, Markus; Glawe, Katrin; Knurr, Moritz; Oevel, Gudrun
September 2023

Inklusion und Digitalisierung im OER-Format lernen, weiterentwickeln und verbreiten – Lehrer:innenbildung als Open Educational Practice (OEP) gestalten. Das Projekt InDigO. Beitrag im Rahmen der Transfertagung: Wege zu einer Kultur des Teilens. Transfertagung des Projekts InDigO an der Universität Paderborn - Büker, Petra; Oevel, Gudrun; Kamin, Anna-Maria; Miller, Susanne
November 2023

Vielfalt als Herausforderung in Unterricht und Ausbildung. Möglichkeiten des Vielfaltstableaus für fallbasiertes, kooperatives Lernen. Impulsvortrag und Gestaltung eines Pädagogischen Tages zur Implementation des Kerncurriculums 2021 mit Seminarausbilder:innen des Zentrums für schulpraktische Lehrer:innenbildung Lüdenscheid - Büker, Petra
April 2023

Gemeinsam sind wir stark! Partizipation von Schülerinnen und Schülern am Kinderschutz. Impulsvortrag an der Schulleitervollversammlung des Kreises Paderborn zum Thema: Schutzkonzepte in Schulen – Kindesschutz geht nur zusammen. Paderborn - Büker, Petra
Oktober 2023

Aktuelle Lehrer:innenbildung für Inklusion. Ausgangspunkte, Herausforderungen und Gestaltungsmöglichkeiten für studienganggemischte Seminargruppen. Impulsvortrag am Zentrum für Lehrkräftebildung, Universität Duisburg-Essen - Büker, Petra
Juni 2023

Inklusion auf neuen Wegen lehren und lernen: Grundschullehrkräftebildung mit Open Educational Resources (OER) im Format von Open Educational Practices (OEP) - Befunde aus dem Pilotprojekt InDigO. Posterbeitrag auf der Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Siegen - Büker, Petra; Herding, Jana; Bernasconi, Bernadette; Becker, Veronika; Glawe, Katrin
September 2023

Paderborner Qualitätsstern (PQ³): A self-evaluation instrument for ECEC and school educators to reflect collaboration in transition processes. Current findings. Presentation on the EECERA Conference "Children´s Curiosity, Agency and Participation: challenges for professional Action and Development" in Lisbon (Portugal) - Büker, Petra; Höke, Julia; Herding, Jana
September 2023

Children’s Voices concerning their Role as Researchers. Implications for Participation, Curiosity and Agency. Presentation on the EECERA Conference "Children´s Curiosity, Agency and Participation: challenges for professional Action and Development" in Lisbon (Portugal) - Büker, Petra; Fernhomberg, Hannah Marie
September 2023

Querschnittsthemen in der Hochschullehre professionalisierungswirksam vernetzen. Beitrag auf der TURN Conference „Prototyp Zukunft – Lösungen für transformative Lehre teilen“ an der TH Köln - Büker, Petra; Wistuba, Frank; Glawe, Katrin; Knurr, Moritz
September 2023

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Facial Recognition in Law Enforcement - Hälterlein, Jens (The Oxford Handbook of the Sociology of Machine Learning)
Abstract This chapter discusses the use of facial recognition technology (FRT) by law enforcement with a special focus on machine learning applications. First, FRT is situated in the larger context of the rise of video surveillance and a shift in Western security culture. The chapter shows how the promise of FRT addresses the problems of video surveillance. Then, it explains how FRT works and how machine learning techniques such as eigenface and convolutional neural networks come into play. Afterward, it explains how the accuracy and effectiveness of FRT are evaluated and why it is important to take the interplay of human operators and FRT systems into account. Finally, several controversies around the police use of FRT are presented and the limits of technological solutions to the problem of bias are demonstrated.

The use of AI in domestic security practices - Hälterlein, Jens (Handbook of Critical Studies of Artificial Intelligence)

Leibniz, Zeitschrift für Didaktik der Philosophie und Ethik

Kants kategorischer Imperativ im sprachsensiblen Philosophieunterricht. Sapere Aude – Habe Mut, dich Primärquellen zu bedienen. (gekürzt) - Albus, Vanessa; Jost, Leif Marvin (Textarbeit im Philosophie- und Ethikunterricht)

Humanismus und Philosophieunterricht - Albus, Vanessa (Humanität als religionspädagogisches und -didaktisches Leitmotiv)

Leibniz. Ein Rationalist im Kanon des Philosophieunterrichts - Albus, Vanessa; Blank, Andreas (ZDPE)

Barbara Schmitz: Was ist ein lebenswertes Leben? Philosophische und biographische Zugänge. Stuttgart Reclam 2022 - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Methodenentwicklung zur Prognose des Crashverhaltens von widerstandspunktgeschweißten 3-Stahlblechverbindungen - Olfert, Viktoria; Schuster, Lilia; Bähr, Philipp; Hein, David; Meschut, Gerson; Sommer, Silke
Die aktuellen politischen und wirtschaftlichen Rahmenbedingungen zur Reduzierung der CO2-Emissionen sowie der Trend zur flächendeckenden Elektromobilität führen zu einer Vielzahl an neuen Herausforderungen für die Auslegung zukünftiger Fahrzeugkonzepte. Eine besondere Herausforderung ist das durch die Batterie ins Fahrzeug eingebrachte Zusatzgewicht. Hierdurch ergibt sich ein Konflikt zu der bestehenden Kundenerwartung nach einer hohen Reichweite. Durch den umfangreichen Einsatz von höchstfesten Stählen in dünnen Blechdicken im Karosseriebau soll die Reduzierung des Gesamtfahrzeuggewichts vorangetrieben werden. Vor allem im stahlintensiven Leichtbau ist das Widerstandspunktschweißen aufgrund des hohen Automatisierungsgrads, der Prozesssicherheit und der damit verbundenen Wirtschaftlichkeit das dominierende Fügeverfahren. Um Begrenzungen des Bauraums der Karosserie zu begegnen und um den Materialeinsatz im Leichtbau möglichst effizient zu gestalten, werden mehrschnittige Punktschweißverbindungen eingesetzt. Hieraus ergeben sich neue Herausforderungen für die Vorhersage des Trag- und Versagensverhaltens unter Crashbelastung. Dieser Beitrag stellt eine systematische Charakterisierung von 3-Blechverbindungen zur Auffindung von formelmäßigen, empirischen Zusammenhängen zwischen der Festigkeit der Verbindung und den Einflussgrößen vor. Nach der Identifikation geeigneter Einflussgrößen, wie zum Beispiel Blechfestigkeit, Blechanordnung, Blechdickenkombination sowie Belastungsart und Lasteinleitung, auf das Trag- und Versagensverhalten, werden numerische Simulationen durchgeführt, um Ursachen für auftretende Phänomene aus den experimentellen Ergebnissen aufzuklären. Weiterhin wird untersucht, inwieweit das Verhalten von 2-Blechverbindungen auf 3-Blechverbindungen übertragbar ist. Die gefundenen Zusammenhänge sollen schnelle und kostengünstige Abschätzungen über die Festigkeit von 3-Blechbverbindungen ermöglichen. Darüber hinaus werden Ersatzmodelle für die Crashsimulation von 3-Blechverbindungen entwickelt, die recheneffizient für die Sicherheitsbewertung von großen, geschweißten Bauteilen eingesetzt werden können. Dabei sollen insbesondere die Einflüsse des Lastangriffs an jeweils einer oder beiden Fügebenen auf die Festigkeit und Energieabsorption unter verschiedenen Belastungen wie Zug, Scherung sowie Biegung abbildbar sein.

Altis-SYCL: Migrating Altis Benchmarking Suite from CUDA to SYCL for GPUs and FPGAs - Weckert, Christoph; Solis-Vasquez, Leonardo; Oppermann, Julian; Koch, Andreas; Sinnen, Oliver (Proceedings of the SC '23 Workshops of The International Conference on High Performance Computing, Network, Storage, and Analysis)

Enabling Reconfigurable HPC through MPI-based Inter-FPGA Communication - Contini, Nicholas; Ramesh, Bharath; Kandadi Suresh, Kaushik; Tran, Tu; Michalowicz, Ben; Abduljabbar, Mustafa; Subramoni, Hari; Panda, Dhabaleswar (Proceedings of the 37th International Conference on Supercomputing)

Shallow Water DG Simulations on FPGAs: Design and Comparison of a Novel Code Generation Pipeline - Alt, Christoph; Kenter, Tobias; Faghih-Naini, Sara; Faj, Jennifer; Opdenhövel, Jan-Oliver; Plessl, Christian; Aizinger, Vadym; Hönig, Jan; Köstler, Harald (Lecture Notes in Computer Science)

A computation of D(9) using FPGA Supercomputing - Van Hirtum, Lennart; De Causmaecker, Patrick; Goemaere, Jens; Kenter, Tobias; Riebler, Heinrich; Lass, Michael; Plessl, Christian (arXiv:2304.03039)
This preprint makes the claim of having computed the $9^{th}$ Dedekind Number. This was done by building an efficient FPGA Accelerator for the core operation of the process, and parallelizing it on the Noctua 2 Supercluster at Paderborn University. The resulting value is 286386577668298411128469151667598498812366. This value can be verified in two steps. We have made the data file containing the 490M results available, each of which can be verified separately on CPU, and the whole file sums to our proposed value.

Approximate simulation of the hysteresis friction of radial shaft seals - Bührmann, Tobias; Magyar, Balázs (64. Tribologie-Fachtagung 2023)

"Aus jedem jungen Munde erklingt das gleiche Lied." – Die Vergemeinschaftung der Hitler-Jugend mit und in nationalsozialistischen Liedern - Schubert, Katrin (Kommunikative Praktiken im Nationalsozialismus)

Umgang mit Evidenzen angehender Lehrkräfte in den Naturwissenschaften - Epistemologie in der Lehrkräfteausbildung - Pollmeier, Pascal
Eine Forderung nach evidenzbasierter Praxis (EBP) im Bildungswesen kann sowohl vor dem Hintergrund der Bedeutung wissenschaftlicher Evidenzen innerhalb gesellschaftlicher Diskurse als auch der Evidenzbasierung in anderen Bereichen formuliert werden. Der Umgang mit und die Bewertung von Evidenzen stellen somit vor dem Hintergrund epistemologischer Überzeugungen relevante Aufgaben für den Chemieunterricht dar. Dabei ist unklar, inwiefern (angehende) Lehrkräfte über Kompetenzen in EBP verfügen. Bestehende Studien weisen auf einen Bedarf der fachdidaktischen Analyse und Förderung von Kompetenzen in EBP bei angehenden Lehrkräften hin.Im Rahmen dieser Dissertation wurde die Domänenspezifität der Kompetenzen in EBP sowie deren Förderung in einem fachdidaktischen Kontext untersucht. Dabei wurde ein weiterer Schwerpunkt auf den Umgang mit anomalen Beobachtungen im Sinne widersprüchlicher Evidenzen gelegt. Innerhalb von drei Teilstudien wurden unterschiedliche methodische Zugänge zur Kompetenz in EBP auf Grundlage epistemologischer Überzeugungen gewählt.Die Ergebnisse weisen auf einen Förderbedarf der Kompetenz in EBP für angehende Lehrkräfte aller Unterrichtsfächer hin. Eine entwickelte Intervention für angehende Chemielehrkräfte weist eine Wirksamkeit zur Förderung von Kompetenzen in EBP auf. Im Rahmen einer Modellierungsstudie kann der Einfluss von Fachwissen sowie Indizien für einen Einfluss epistemologischer Überzeugungen auf den Umgang mit anomalen Beobachtungen gezeigt werden.
Keywords: Epistemologie; Evidenzen; evidence-based practice

Pädagogische Beobachtungen. Eine Seminareinheit zur Förderung von Beobachtungskompetenz: Protokolle erstellen, kriteriengeleitet analysieren und Peer-Feedback formulieren - Kottmann, Brigitte; Pieper, Catania; Miller, Susanne; Reh, Anne (DiMawe -Die Materialwerkstatt)